Comparative Floral Characters, Pollinator Limitation, and Pollination Success in Different Habitats of Caragana microphylla Lam - Chen, Min; Zuo, Xiao-an; Zhao, Xue-yong (Frontiers in Ecology and Evolution, 2020)
Caragana microphylla Lam plays an important role in desert-grassland revegetation. Plant reproduction in arid regions may be restricted due to the low abundance or visiting frequency of pollinators. We tested the visited flowers, the pollinated flowers and seed production to estimate how pollinator limitation affects the seed numbers of visited and pollinated flowers. We investigated the floral characters, pollinator activities and breeding systems of C. microphylla. Our results showed that pollinator limitation was the dominant limiting factor in seed production. In addition, floral characters were moderately positively correlated, and more open flowers with large corollas and long spurs were observed in the natural plots than in grazed plots. Apis mellifera was the most important pollinator. Our findings further indicate that the number of opening flowers and rate of pollinator visitation were positively correlated. In C. microphylla, insect pollination was dominant in outcrossing, and self-pollination played a supporting role in ensuring successful pollination. This study provides a better understanding of how grazing habitat affects floral characters, pollinator limitation, and pollination success of C. microphylla.